Treatises About the Subterranean World in Ljubljana Between 1678 and 1773 - Južnič, Stanislav (Acta Carsologica, 2016)
Popisali smo knjige, razprave in rokopise o podzemeljskih in kraških pojavih, ki so bile na voljo v Ljubljani v času delovanja jezuitskega kolegija. Preučili smo Mayrjev prodajni katalog iz leta 1678. Pregledali smo knjige, ki so jih nabavljali za jezuitsko in druge knjižnice v Ljubljani. Posebno pozornost smo posvetili doslej neraziskanim objavljenim delom in rokopisom ljubljanskih jezuitov. Pokazali smo, kako je v Ljubljani nakopičeno znanje pripomoglo k nastanku pionirskih del modernega krasoslovja v zadnji četrtini osemnajstega stoletja. We researched the books, papers, and manuscripts about the subterranean and karst phenomena available in Ljubljana in the time of Jesuit college. We used the data from Mayr’s book catalogue of 1678. We analyzed the books in the Jesuit and other Ljubljanese libraries. For the first time in historiography the special concern was put on published works and manuscripts of the Ljubljanese Jesuits. We described how the knowledge accumulated in Ljubljana paved the way for pioneering karstology research in the last quarter of the 18th century.